Be aware of suicide risk among female student‐veterans. Issue 7 (23rd October 2017) - Sutton, Halley
Abstract : Female veterans are 250 percent more likely to commit suicide than their civilian peers, according to a report from the Department of Veterans Affairs. The report, which analyzed more than 55 million veteran records from 1970–2014, found that female veterans aged 18–29 were the most likely to commit suicide, a prime age demographic for student‐veterans on campus. According to the report, an average of 20 veterans, both male and female, died from suicide each day in 2014, and the states with the highest suicide rates were Montana, Utah, Nevada, and New Mexico.